Financial Wellbeing of Micro-entrepreneurs and the Business Performance of Microenterprises in the Philippine Summer Capital as Functions of Human Capital and Financial Resource Capability - Bautista, Lerma Butigan (Animo Repository, 2023)
The study of human capital including general background, management knowhow, specific industry knowhow, entrepreneurial orientation, and financial capability that includes financial literacy and financial behavior are essential in investigating the financial wellbeing and business performance of entrepreneurs as it is paramount to study the effect of financial resource capability. Entrepreneurs contribute income and innovations, and play a major role in economic development as they create jobs, products, and services. They generate economic benefits that may even be greater than the benefits they enjoy with their provision of the largest employment opportunities around the world and their contribution of substantial business output. However, they account for a small market share and most do not continue to operate for a longer period as larger businesses do. Most micro-enterprises are one-man enterprises so firms are believed to mirror the owners. This study investigated the business performance of microenterprises in the Philippine Summer Capital as it examined the financial wellbeing of the micro-entrepreneurs applying the Human Capital Theory and the Resource-Based View Theory. Grounded on the positivist philosophy, a quantitative approach was employed to analyze empirical data. Data were gathered from four hundred micro-entrepreneurs through questionnaires and interviews with Department of Trade and Industry representatives. Responses to open-ended questions and interviews were not statistically analyzed but were utilized to enrich the discussion of the concepts being investigated. The results revealed that saving behavior significantly predicted the financial wellbeing of the micro-entrepreneurs while having managerial experience, entrepreneurial orientation, and financial resource capability significantly affected business performance. Nevertheless, analyses of confidence intervals, effect sizes, responses to open-ended questions, and interviews revealed the importance of higher levels of financial literacy, spending behavior, and budgeting behavior in attaining higher levels of financial wellbeing and business performance. These were further analyzed to arrive at more comprehensive and practical recommendations. Responses to the open-ended questions and interview questions also emphasized the importance of financial resource capability and entrepreneurial orientation. Moreover, other factors like mental budgeting, attendance to informal business-related education and training, and “diskarte” were discovered. The financial wellbeing of the micro-entrepreneurs and the business performance of the microenterprises were significantly correlated. Financial behavior partially mediated the relationship between financial literacy and financial wellbeing, and financial behavior fully mediated the relationship between financial literacy and business performance. The micro-entrepreneurs described financial wellbeing and financial distress, and they identified their needs and approaches in improving business performance. Meanwhile, the financial literacy questions may not have captured the financial literacy of the micro-entrepreneurs in terms of their investment skills. They scored low in sophisticated financial literacy questions for their illiteracy in stocks and bonds but the micro-entrepreneurs invest in commodities, properties, and in other businesses.